The Enhancement of Immunity Gained from Feline Trivalent Vaccines in Mice Using Feline IL-15, IL-23 and Metabolic Regulatory Molecules - Ruichen Gao; Wei Sun; Danning Zhang; Linhan Zhang; Dafang He; Mengxi Li; Yi Wei; Junjie Peng; Gang Wang (Biology, 2025)
The feline calicivirus, herpesvirus, and panleukopenia viruses are major infections that cause serious diseases in cats; however, current trivalent vaccines have limitations in immune efficacy and their duration of protection. This study assesses the immune-enhancing effects of novel adjuvants (feline IL-15, IL-23, and metabolic modulators) on vaccine responses. Forty mice were randomly assigned to four groups: Group A (composite adjuvants), Group B (metabolic regulatory molecules and Mn adjuvant), Group C1 (Mn adjuvant), and Group C2 (a blank commercial vaccine). The results showed that Group A had significantly higher neutralizing antibody titers against calicivirus post-booster immunization, while both Groups A and B exhibited enhanced antibody responses against the herpesvirus and panleukopenia viruses. Notably, Group A displayed increased proportions of memory T cells, follicular B cells, and activated B cells. These findings suggest that the combination of feline IL-15, IL-23, and metabolic modulators are safe and effective immunoadjuvants for trivalent feline vaccines to promote immune cell differentiation and antibody production, thus representing a promising strategy to optimize vaccine efficacy.